Transbronchial lung biopsy in cancer diagnosis - Świerkocki, Krzysztof; Nowicka, Małgorzata; Cofta, Szczepan; Piorunek, Tomasz; Młynarczyk, Witold (Contemporary Oncology/Współczesna Onkologia, 2002)
Transbronchial lung biopsy (TBLB) is an invasive method of diagnosis of both solid pulmonary lesion and disseminated pulmonary changes. During the procedure forceps biopsy of extra-bronchial changes is performed. Correct positioning of a fiberoptic bronchoscope and forceps is assured and guided by chest fluoroscopy. The complications of TBLB are rare and include: haemophysis and pneumothorax. Rarely either of these requires intensive treatment. The aim of this study was to assess the usefulness of fluoroscopy guided transbronchial lung biopsy in the diagnosis of possible lung malignancies. Between May 2000 and May 2001 in the Department of Pulmonary Diseases University of Medical Sciences in Poznań lung biopsies were done in 39 patients suspected of pulmonary malignancies. They were 32 males and 7 females and their age varied from 30-78 years. There were different imaging techniques used in the assessment of lung change character and localisation. All the patients had conventional chest radiographs (both posteroanterior and lateral films) performed, some tomograms or computed tomography of the chest. The procedures were performed in radiology laboratory after the patient was premedicated. Fiberoptic bronchoscope was inserted through nasal passage, and upper airways and bronchial tree was evaluated. Then forceps were introduced through the bronchoscope to the region with change. The position of biopsy forceps was controlled with the use of fluoroscopy both in patients'; supine and lateral position. Between 1-3 bioptats were obtained and broncho-alvelolar lavage performed. After the procedure bronchi were checked for bleeding (using bronchoscope) and pneumothorax excluded (with the use of fluoroscopy). Tissue specimens were assessed by a pathologist. In 27 patients (69,2%) lung cancer was diagnosed, interstitial fibrosis in two patients, in one patient - tuberculosis and also in one patient - sillicosis. In 8 patients (20.5%) no pathological changes were found. No patient developed pneumothorax. All the patients had haemoptisis after the biopsy, but only 7 patients required antihaemorrhagic treatment. Transbronchial lung biopsy is an effective method in diagnosis of pulmonary malignancies. In many cases it diminishes the need for more invasive surgical diagnostic methods.